Environmental management, cleaner production and organizational performance: case of Colombia - Palacio, Sandra L. (Pontificia Universidad Católica del Perú, 2019)
Organizations can redirect their business models to solve the problem of materials depletion using environmental management and cleaner production as practices of the circular economy. This study aimed to measure the relationship between environmental management, cleaner production, and organizational performance. Within this context, a survey of 372 companies was conducted in the agro-industrial, manufacturing, construction sectors in three important productive regions of Colombia. These three sectors were defined because they belong to the real productive sector and represent a greater participation in the country’s gross domestic product. Structural equation modeling was used for data analysis. The economic sector moderated the relationship between the latent variables. This phenomenon was analyzed using a multi-group technique. The results showed that cleaner production was positively related to organizational performance at corporations. It was also observed that environmental management influenced cleaner production. Finally, it is worth noting that productive sectors in Colombia tend to be committed to circular economy practices, some to environmental management and others to cleaner production with an impact on organizational performance. These findings will be extremely useful for promoting future research studies with regard to establishing a better framework for promoting environmental management and cleaner production practices primarily among Colombian productive companies as this work can also serve as a reference for other industrial sectors and other countries.
Keywords: Medio ambiente--Colombia; Investigación cuantitativa; https://purl.org/pe-repo/ocde/ford#5.02.04